Penampilan Reproduksi (Service Per Conception, Lama Kebuntingan Dan Selang Beranak) Kambing Boerawa Di Kecamatan Gedong Tataan Dan Kecamatan Gisting - Adi Sulaksono; Sri Suharyati; Purnama Edy Santosa (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2012)
The purpose of this research is to know data about the reproduction performance (service per conception, conception rate and calving interval) of Boerawa goat in Gedong Tataan and Gisting District. This research used survey method. The primary and secondary data was used analyzed by descrptively. The result showed that the service per conception in Gedong Tataan District is 1,35 and in Gisting District is 1,34; conception rate in Gedong Tataan District is 157,1 days and in Gisting District in 154,7 days; and calving interval in Gedong Tataan District is 277,123 days and in Gisting District is 240,245 days. Key words: Boerawa Goat, service per conception, conception rate, calving interval